Myth or reality : unpacking the contribution of indigenous knowledge systems in solving sexual health problems in Zimbabwe: case of Bulawayo from 2006 to 2015 - Sibanda, God'swords (Midlands State University, 2018)
Indigenous knowledge systems have been part and parcel of the African people’s lives and they still continue to inform much of their lives. These knowledge systems have been marginalized since the colonial era. This study serves to prove the myths and realities associated with indigenous knowledge systems in curing sexual health problems in Zimbabwe, case of Bulawayo. The missionaries and colonial officers collaborated to alienate and marginalize African indigenous knowledge system so as to promote the western culture. Sexual health problems are one of the nagging health complications developing countries face. A lot of individual suffer from sexual health problems in silence, because the subject of sexuality is considered a taboo in the African society. This research focused on the socio-economic implication of sexual health problems and efforts by different stake holders in trying to revive indigenous knowledge systems and improve its status. The research made use of interviews, observation, newspapers and secondary sources to come up with a candid and objective analysis of the contribution of indigenous knowledge systems in solving sexual health problems and the role of concerned players in reviving indigenous knowledge systems. The main findings were that women and adolescents are the most affected by the impact of sexual health problems. Also discovered is the ambiguous attitude of the government towards traditional health system and the professionalization of traditional health system through ZINATHA.